Tropicália and Beyond: Dialogues in Brazilian Film History, editado por Stefan Solomon - Carréra, Guilherme (Imagofagia, 2021)
Sobre Solomon, Stefan (Ed.). Tropicália and Beyond: Dialogues in Brazilian Film History. Berlim: Archive Books, em parceria com a University of Reading, 2017, 301 pp.